Productivity and distribution effects of codetermination in an efficient bargaining - Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Codetermination can be regarded as an extreme regulatory intervention of the legislator in the labor market which might affect the efficiency of production and the bargaining power of labor. Based on a model that covers both efficient bargaining and employment bargaining a simple equation is derived that is suited to empirical testing. The empirical test is based on German data and includes years before and after the extension of German codetermination law in 1976. The estimates determine the productivity of labor and relative bargaining power of capital and labor. It turns out that codetermination does not affect productivity, but leads to a significant increase in workers' bargaining power and the distribution of rents.
urn:nbn:de:bsz:180-madoc-435964
Keywords: L22; L23; J52; J53; 330; codetermination; productivity; wage-bill share; bargaining